1998
DOI: 10.1021/bi971732f
|View full text |Cite
|
Sign up to set email alerts
|

The Lon Protease from Mycobacterium smegmatis:  Molecular Cloning, Sequence Analysis, Functional Expression, and Enzymatic Characterization

Abstract: We have charterized a Mycobacterium smegmatis gene encoding a homolog of the ATP-dependent protease Lon (La). Our identification of a Lon homolog, in conjunction with our previous work, identifies M. smegmatis as the first known example of a eubacterium containing both Lon and a complete 20S proteasome (containing both alpha- and beta-subunits). Despite the significant primary sequence divergence between M. smegmatis Lon (Ms-Lon) and E. coli Lon (Ec-Lon), expression of Ms-Lon was only moderately toxic to E. co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 55 publications
1
40
0
Order By: Relevance
“…This result indicated that the ATPase and proteolytic domains function independently but interact structurally. These findings parallel the facts that substitution in the active site Ser nucleophile abolishes the peptidase activities but not the whole ATPase activities of Lon proteases (45)(46)(47). By contrast, Bt-Lon⌬N retained less than 1% of ATPase activity and only 1 Ϯ 0.5 and 2 Ϯ 0.3% of protease and peptidase activities, respectively, compared with those of the wild type.…”
Section: Design Of Bt-lon Mutants For Structure-function Studies-supporting
confidence: 77%
See 1 more Smart Citation
“…This result indicated that the ATPase and proteolytic domains function independently but interact structurally. These findings parallel the facts that substitution in the active site Ser nucleophile abolishes the peptidase activities but not the whole ATPase activities of Lon proteases (45)(46)(47). By contrast, Bt-Lon⌬N retained less than 1% of ATPase activity and only 1 Ϯ 0.5 and 2 Ϯ 0.3% of protease and peptidase activities, respectively, compared with those of the wild type.…”
Section: Design Of Bt-lon Mutants For Structure-function Studies-supporting
confidence: 77%
“…However, Smith et al (35) demonstrated that a small ␣-domain, present in most AAA ϩ modules, acts as a ''sensor and substrate discrimination'' domain. On the other hand, both peptidase and ATPase activities of Lon proteases are stimulated by unfolded proteins such as ␣-casein (47,60). The existing working model of Lon proteases indicates that the ␣-casein interaction site also resides in the N-terminal domain (5,61), which has been termed previously the allosteric site (or initiator site) (57,59).…”
Section: The N-terminal Domain Of Lon Proteases Is Essential Formentioning
confidence: 99%
“…HspR controls expression of the hsp70 and clpB genes in Mycobacterium tuberculosis and Mycobacterium leprae, but these bacteria do not contain any gene orthologous to lon. However, lon orthologues have been found in other mycobacteria, such as Mycobacterium smegmatis (Roudiak et al, 1998), and genome analysis revealed HAIR motifs upstream of lon in M. smegmatis, suggesting that the HAIR\HspR regulation of lon may be widespread among actinomycetes. Although Streptomyces spp.…”
Section: Discussionmentioning
confidence: 99%
“…The first discovered of these proteases and probably the most intensively studied biochemically is Lon (also called La) (4,5). Genes encoding Lon protease have been found in a large variety of prokaryotes, where they have been implicated in developmental pathways, as well as in the degradation of specific regulatory proteins (see below) (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). In eukaryotes, Lon is found in mitochondria and has been shown to be essential for mitochondrial function in Saccharomyces cerevisiae (18)(19)(20)(21).…”
mentioning
confidence: 99%
“…In Lon, a consensus site for ATP binding and hydrolysis has been shown by mutation to be necessary for proteolysis and ATPase activity; mutations in the active site serine ( Fig. 1) block proteolysis but do not fully abolish ATPase activity (14,(26)(27)(28)(29)(30). How and where substrate binding takes place and how substrates are presented to the active site, however, have not been clarified, and very few mutations other than those in the serine or ATPase sites have been described.…”
mentioning
confidence: 99%